Cellulose Biomass Conversion - van de Ven, Theo; Kadla, John (IntechOpen, 2013)
Cellulose is only one of the components of biomass, although being the most abundant. To make useful chemicals or materials from cellulose requires as the first step the separation of cellulose from biomass. Various issues of cellulose extraction and its conversion are discussed in the chapters of this book on cellulose, the third and last one of a series of books on cellulose. This conversion of cellulose is an integral part of the biorefinery concept, an effort to derive optimum value from all biomass components, and as such compulsory reading for students and researchers in this area.